Health professional's perceptions of sexual assault management: A Delphi study - Jancey, Jonine; Meuleners, Lynn; Phillips, Maureen (Sage Publications, 2011)
Objective: To explore health professionals’ perceptions of sexual assault management practices and identify issues related to these practices across Western Australia (WA).Design: A two-round electronic Delphi study was undertaken with health professionals (medical doctors, registered nurses, social workers and managers). Setting: Healthcare settings (emergency departments and community health centres) located in metropolitan Perth and rural WA.Methods: Snowball sampling methodology was used to recruit 27 participants. The first round questionnaire asked about perceptions of sexual assault management practices in WA and how to improve them. The round two questionnaire asked panellists their agreement to the identified issues and to prioritize solutions to the problems. Results: Out of the 14 issues identified, three issues gained 100 per cent agreement: limited services/resources in regional areas of WA; a shortage of culturally appropriate services; and the treatment of victims/survivors of sexual assault within the legal system. The main solutions included: a detailed manual providing clear guidelines; a flow chart detailing forensic data collection; improved services to support sexual assault cases; and a multi-sectorial management approach to sexual assault. Conclusions: There is a need for a comprehensive management approach to sexual assault which includes clear prescriptive guidelines; workforce training and development; equitable access to services; and community education. Sexual assault is a serious public health issue. The adoption of a multilevel approach will support change and improve health outcomes for this group.